2018
DOI: 10.1021/acs.est.8b02831
|View full text |Cite
|
Sign up to set email alerts
|

Halobenzoquinone-Induced Developmental Toxicity, Oxidative Stress, and Apoptosis in Zebrafish Embryos

Abstract: The developmental toxicity of water disinfection byproducts remains unclear. Here we report the study of halobenzoquinone (HBQ)-induced in vivo developmental toxicity and oxidative stress using zebrafish embryos as a model. Embryos were exposed to 0.5-10 μM of individual HBQs and 0.5-5 mM haloacetic acids for up to 120 h postfertilization (hpf). LC values of the HBQs at 24 hpf were 4.6-9.8 μM, while those of three haloacetic acids were up to 200 times higher at 1900-2600 μM. HBQ exposure resulted in significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 60 publications
6
55
1
Order By: Relevance
“…Furthermore, the study showed that brominated and iodinated DBPs tended to be more toxic than their chlorinated analogues [45]. Wang et al tested the toxicity of halobenzoquinones, which are an emerging class of DBPs that have been detected in drinking water and swimming pool water [46]. They exposed zebrafish embryos to these compounds and compared the effects of halobenzoquinones to those found in zebrafish embryos exposed to HAAs.…”
Section: Non-human Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study showed that brominated and iodinated DBPs tended to be more toxic than their chlorinated analogues [45]. Wang et al tested the toxicity of halobenzoquinones, which are an emerging class of DBPs that have been detected in drinking water and swimming pool water [46]. They exposed zebrafish embryos to these compounds and compared the effects of halobenzoquinones to those found in zebrafish embryos exposed to HAAs.…”
Section: Non-human Animalsmentioning
confidence: 99%
“…They showed that halobenzoquinones induced reactive oxygen species (ROS) generation and inhibited the antioxidative response of cells in developing zebrafish, resulting in death, physical malformations, oxidative DNA damage, and apoptosis. They also determined that the acute toxicity and ROS induction of halobenzoquinones was up to 200 times more potent than those induced by HAAs [46] (Table 2).…”
Section: Non-human Animalsmentioning
confidence: 99%
“…Via quantitative structural toxicity relationship modeling, toxicity of HBQs is demonstrated to be 1000 times higher than that of regulated DBPs such as THM and HAA (Bull et al (2007). It was shown that HBQs exert higher cytotoxicity, genotoxicity, and developmental toxicity than that of regulated DBPs (Li et al, 2015;Li et al, 2016;Wang et al, 2018). Therefore, the presence of HBQs in drinking water is an emerging threat to public health.…”
Section: Introductionmentioning
confidence: 99%
“…However, systematic quantitative toxicological analyses of ~ 80 DBPs by Plewa and colleagues indicated that the N-DBPs are more toxic than C-DBPs (Muellner et al, 2007;Jeong et al, 2015). Moreover, some halogenated aromatic DBPs with higher toxicity than halogenated haloaliphatic DBPs were identified and quantified in various drinking water samples, ranged from several ng/L to a few μg/L (Pan and Zhang, 2013;Pan et al, 2014;Wang et al, 2018). Therefore, the toxic effect of N-DBPs and halogenated aromatic DBPs cannot be ignored because toxicity relies upon their concentration and toxic potency.…”
Section: Introductionmentioning
confidence: 99%